2008
DOI: 10.1016/j.dss.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A model to develop effective virtual teams

Abstract: A review of the literature shows the factors that impact on the effectiveness of virtual teams are still ambiguous. To address this problem we developed a research design that included a meta-analysis of the literature, a field experiment and survey. The meta-analysis identified factors which impact on the effectiveness of virtual teams which were then validated by a field experiment and survey. The results of the study indicate that social dimensional factors need to be considered early on in the virtual team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(152 citation statements)
references
References 118 publications
(118 reference statements)
8
142
0
2
Order By: Relevance
“…Team cohesion allows group members to communicate more effectively to coordinate their efforts (Evans & Jarvis, 1980). Furthermore, virtual team research has emphasized that social factors such as relationship building, cohesion and trust, are crucial for the effectiveness of virtual teams (e.g., Gillam & Openheim, 2006;Lin et al, 2008). Previous studies identified the positive outcomes of team cohesion, such as enhanced motivation, better decisions, more open communication and higher satisfaction among team members (Andrews, Kacmar, Blakely, & Bucklew, 2008;Warkentin & Beranek, 1999).…”
Section: Team Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…Team cohesion allows group members to communicate more effectively to coordinate their efforts (Evans & Jarvis, 1980). Furthermore, virtual team research has emphasized that social factors such as relationship building, cohesion and trust, are crucial for the effectiveness of virtual teams (e.g., Gillam & Openheim, 2006;Lin et al, 2008). Previous studies identified the positive outcomes of team cohesion, such as enhanced motivation, better decisions, more open communication and higher satisfaction among team members (Andrews, Kacmar, Blakely, & Bucklew, 2008;Warkentin & Beranek, 1999).…”
Section: Team Processesmentioning
confidence: 99%
“…Communicating and exchanging information also improves coordination, which is expressed through group cohesion and shared goals (Baker, 2002;Lin et al, 2008;Tekleab, Quigley, & Tesluk, 2009). This suggests a positive relationship between intra-team communication and Team cohesion (Kozlowski & Ilgen, 2006) represents a multifaceted phenomenon and is defined as "attraction to the group, satisfaction with other members of the group, and social interaction among the group members" (O'Reilly, Caldwell, & Barnett, 1989, p. 22).…”
Section: Team Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…AVE larger than 0.5 is the threshold (McNamara, Dennis, & Carte, 2008). CR is calculated by squaring the sum of loadings, then dividing it by the sum of squared loadings, plus the sum of the measurement error (Lin, Standing, & Liu, 2008). CR should be greater than 0.6 (Huang, 2009).…”
Section: Criteria For Model Fitmentioning
confidence: 99%
“…However, it is truly a challenge to be able to communicate regularly and timely when working on virtual teams due to several factors such as cultural, social and time differences. Communication and collaboration are believed to positively impact the social aspect of the virtual teams by improving the team performance as well as satisfaction levels between the members 12 . Furthermore, collaboration in a virtual environment poses a number of unique difficulties, as Michael She 19 asserted, such as "feedback latency, reduced accuracy in comprehension, and technical challenges that impede effective communication."…”
Section: Literature Reviewmentioning
confidence: 99%